Development of Lecturer Performance Assessment Instruments through the Plomp Model in Higher Education - Sitti Zuhaerah Thalhah; Tasdin Tahrim; Reski Elvira Sari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to examine the process of developing performance appraisal instruments and descriptions by referring to the lecturers of the Mathematics Tadris Study Program IAIN Palopo and analyzing their responses. This type of investigation uses research and development (Research and Development). Four phases follow it in the Plomp development model: the first phase, which is investigation-based; then there is the design phase; then there is the realization phase; then there are the test and evaluation phases. And finally, there is a revision phase. The results showed that the percentage of lecturers' performance by category, namely 14.28% was in the very high category, 57% was in the high category, 28.72% was in a low category, and 0% was in the deficient category. This shows that maximum efforts are needed to improve the performance of lecturers so that they are even more optimal in the implementation of the tri dharma of higher education in the Mathematics Tadris Study Program IAIN Palopo. This study implies the importance of understanding the performance appraisal mechanism for each lecturer so that it can be used as a basis for improvement and career development.